Penerapan Metode Pembelajaran Outing Class Dalam Meningkatkan Kecerdasan Naturalis Siswa Kelas III SD Negeri 0104 Sibuhuan - Rhamdan; Yuli Marlina; Era Mutiah (Yayasan Perguruan Kampus, 2025)
Based on the research results, it can be concluded that: (1) The natural intelligence of grade III students of SD Negeri 0104 Sibuhuan in the pre-cycle was only 2 students or 9.52% with “very good” natural intelligence, 4 students or 19.05% with “good” natural intelligence, 6 students or 28.57% with “sufficient” natural intelligence, 8 students or 38.10% with “less” natural intelligence and 1 student or 4.76% with “very less” natural intelligence. (2) The application of the outing class learning method in improving the natural intelligence of grade III students of SD Negeri 0104 Sibuhuan in cycle I was 6 students or 28.57% with “very good” natural intelligence, 8 students or 38.10% with “good” natural intelligence, 7 students or 33.33% with “sufficient” natural intelligence, no “less” natural intelligence and no “very less” natural intelligence. In cycle II, there were 14 students or 66.67% with